Medication adherence, hospitalization, and healthcare resource utilization and costs in patients with pulmonary arterial hypertension treated with endothelin receptor antagonists or phosphodiesterase type‐5 inhibitors. (1st March 2020) - Frantz, Robert P.; Hill, Jerrold W.; Lickert, Cassandra A.; Wade, Rolin L.; Cole, Michele R.; Tsang, Yuen; Drake, William
Abstract : Adherence to therapy for pulmonary arterial hypertension is essential to optimize patient outcomes, but data on real‐world adherence to different pulmonary arterial hypertension drug classes are limited. This retrospective database analysis evaluated relationships between adherence, hospitalization, and healthcare costs in pulmonary arterial hypertension patients treated with endothelin receptor antagonists or phosphodiesterase type‐5 inhibitors. From the IQVIA Adjudicated Health Plan Database, patients with pulmonary arterial hypertension were identified based on diagnostic codes and prescriptions for endothelin receptor antagonists (ambrisentan, bosentan, macitentan) or phosphodiesterase type‐5 inhibitors (sildenafil, tadalafil) approved for pulmonary arterial hypertension. Patients were assigned to the class of their most recently initiated (index) pulmonary arterial hypertension therapy between 1 January 2009 and 30 June 2015. Medication adherence was measured by proportion of days covered; patients with proportion of days covered ≥80% were considered adherent. The proportion of adherent patients was higher for endothelin receptor antagonists (571/755; 75.6%) than for phosphodiesterase type‐5 inhibitors (970/1578; 61.5%; P  < 0.0001). In both groups, hospitalizations declined as proportion of days covered increased. Among adherent patients, those on endothelin receptor antagonists had a significantly lower hospitalization rate than those on phosphodiesterase type‐5 inhibitors (23.1% versus 28.5%, P  = 0. 0218), fewer hospitalizations (mean (standard deviation) 0.4 (0.8) versus 0.5 (0.9); P  = 0.02), and mean hospitalization costs during the six‐month post‐index ($9510 versus $15, 726, P  = 0.0318). Increasing adherence reduced hospitalization risk more for endothelin receptor antagonists than for phosphodiesterase type‐5 inhibitors (hazard ratio 0.176 versus 0.549, P  = 0.001). Rates and numbers of rehospitalizations within 30 days post‐discharge were similar between groups. Mean total costs were higher with endothelin receptor antagonists than phosphodiesterase type‐5 inhibitors in all patients ($91, 328 versus $72, 401, P  = 0.0003) and in adherent patients ($88, 867 versus $56, 300, P  < 0.0001), driven by higher drug costs.